LFA - LOGISTIC FREIGHT ASSISTANCE USING HADOOP MAP REDUCE FRAMEWORK - Francis, Navya (IJRDO -Journal of Computer Science Engineering, 2015)
In recent years we are using the logistic freight system for the shipping of goods, and these shipping are done by the freight forwarders/carriers from one point to the alternative point. Shipping charges are the freight bills, which has to be paid by the specific organization after the delivery of freight. The freight forwarders/carriers can make mistakes during the preparation of the freight bills. Due to this accurate auditing of the bills has to be prepared otherwise the organization will have to overpay for the services which they haven’t used. Now these auditing is done physically and it require lot of human power and time. Meanwhile there is lot of chance for human and process errors. LFA (Logistic Freight Assistance) is the solution to these problems. It helps to audit the freight bills and using LFA the stakeholders can make informed judgments. It overpowers the human and process errors. The system is developed based on the hadoop mapreduce framework. The data are stored in HDFS and processed using the hadoop map reduce concept